STRATEGIC READING INTERVENTION FOR LEFT-BEHIND LEARNERS IN THE PHILIPPINES - Pocaan, Jordan Miranda; Bailon, Lyndon Lucila; Pocaan, Jean Pauline Trilles (LLT Journal: A Journal on Language and Language Teaching, 2022)
Education for all means no one should be left behind; thus, teachers should provide effective strategies for struggling readers. The “one-size fits all strategy” further divides the gap between the slow and advanced learners. This study used a quantitative observational research design to determine the reading ability of 30 struggling readers in terms of word recognition, reading comprehension, and reading speed using reading stories, Dolch's basic sight words and the Phil-IRI Manual 2018. The study develops strategic reading intervention materials to support teachers and students during the remedial programs. The pre-tests revealed that the reading ability of the struggling readers was at a frustration level. Furthermore, the develop strategic intervention reading materials used in remedial programs were composed of 4 parts: learning content, learning task guide, assessment guide, and enhancement guide. The post-tests show that the participants reading ability progressed to instruction and independent level after the remedial program. It was concluded that determining the student’s present ability is beneficial to develop effective intervention materials. It was suggested that the school leaders and program specialists should develop faculty and student support programs ideally to uplift the student’s literacy.